Stories of dinosaurs - Punter, Russell; Decker, Cynthia (Usborne Publishing Ltd London, 2007)
Three original stories for children who have just started reading on their own. Stories feature wrestling raptors, a hilarious tale of vegetarian dinosaurs and a prehistoric egg hatching in a modern museum. Includes a pronunciation guide to help young readers say the dinosaur names. Humorously illustrated by Cynthia Decker. Part of the Usborne Reading Programme developed with reading experts at the University of Roehampton.